Smooth sailing for Kedah in President Cup match - Noh, Dasheer (The Star, 2013)
KEDAH were in top form to blast six goals past an insipid Kuala Lumpur in a second round President Cup soccer league match at the Universiti Utara Malaysia mini stadium in Sintok, Kedah.